Criteria for selection to anesthesia residency programs: a survey of Canadian anesthesia program directors (Canadian Medical Education Journal, 2021)
Introduction: Applicants to specialty programs lack guidance on knowing what exactly is desired by selection committees and program directors. Anesthesia is especially opaque, given its failure to provide transparency reports nationally. This study was developed to survey Canadian anesthesia program directors about the aspects of the application package desired in an anesthesia applicant. The primary objective is to identify the preferred attributes of anesthesia applications by those mandating the selection committees.Methods: Survey was developed via Google Surveys, and sent online over a period of two months in June and July 2020. All program directors were sent requests for filling in the survey. STATA was used for all statistical analyses. Two analyses, Mann-Whitney and ANOVA tests, were performed for comparison groups. A p < 0.05 was considered significant.Results: Fourteen of seventeen (83%) Canadian anesthesia program directors completed the survey. Having done an anesthesia elective, good performance in it, and excellence of preclinical academic performance were considered among the most important aspects of the application package with the highest ranking important and smallest standard deviation. Any form of red flag was also considered an important criterion, again with little variation among program directors. The reference letters selected by the applicants were also important, with a personal relationship and well written reference being identified as most important (p < 0.05).Conclusions: An applicant who has good academic performance, having anesthesia elective experience, personal, well-written reference letters, and general activity and interests that are not necessarily anesthesia-focused would be favoured by Canadian anesthesia programs.